Increased arterial stiffness in patients with chronic obstructive pulmonary disease: a mechanism for increased cardiovascular risk. Issue 4 (16th November 2007) - Mills, N L; Miller, J J; Anand, A; Robinson, S D; Frazer, G A; Anderson, D; Breen, L; Wilkinson, I B; McEniery, C M; Donaldson, K; Newby, D E; MacNee, W
Abstract : Rationale: Chronic obstructive pulmonary disease (COPD) is associated with a 2–3-fold increase in the risk of ischaemic heart disease, stroke and sudden death. The mechanisms responsible for this association are not clear and appear to be independent of smoking history. Objective: We test the hypothesis that patients with COPD have increased arterial stiffness and blood pressure in comparison with age and smoking matched controls. Methods: In a prospective case control study, we recruited 102 patients with COPD and 103 healthy controls matched for age and smoking status. Patients were assessed by clinical history and spirometry, with arterial stiffness and blood pressure determined using radial artery applanation tonometry and sphygmomanometry. Results: Patients with COPD had increased arterial stiffness compared with matched controls, with elevated augmentation pressure (17 (1) vs 14 (1) mm Hg; p = 0.005) and a reduced time to wave reflection (131 (1) vs 137 (2) ms; p = 0.004). These differences were associated with increases in both diastolic (82 (1) vs 78 (1) mm Hg; p = 0.005) and systolic blood pressure (147 (2) vs 132 (2) mm Hg; p<0.001). Serum C reactive protein concentrations were threefold higher in patients (6.1 (0.9) vs 2.3 (0.4) mg/l; p = 0.001). Data are presented as mean (SEM). Conclusions: Patients with COPD have increased arterial stiffness and blood pressure in comparison with controls matched for age and smoking status. We speculate that increased systemic inflammation and vascular dysfunction could potentially explain the excess cardiovascular morbidity and mortality associated with COPD.